2020
DOI: 10.3390/nu12113336
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Consumption among Portuguese Adults: Potential Drivers and Barriers towards a Sustainable Diet

Abstract: The transition from diets rich in animal products to plant-based protein foods—like pulses—is crucial, for both environmental sustainability and human health. The aim of this study was to characterize the current consumption and to describe the drivers of and barriers to pulse intake in Portugal. Using a quantitative approach, a semi-structured questionnaire was distributed online, and 1174 valid responses were obtained. The most consumed pulses were beans and peas, consumed at least once a week by 48.3% and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
0
17
0
4
Order By: Relevance
“…Low expectations of pulses as dull, tasteless, and gassy have been reported (3,20,23) , although in our sample few concerns over gastric discomfort or distress were offered. Flatulence and intestinal discomfort are more commonly reported elsewhere (20,24) , but there are suggestions that modern canning and preparatory activities can reduce these effects (3,23,24,26) . The intestinal effects of pulse consumption are also thought to decrease with experience (20,24,26) , and notably, in systematic reviews of health impacts, few adverse events of pulse consumption are reported (2) .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Low expectations of pulses as dull, tasteless, and gassy have been reported (3,20,23) , although in our sample few concerns over gastric discomfort or distress were offered. Flatulence and intestinal discomfort are more commonly reported elsewhere (20,24) , but there are suggestions that modern canning and preparatory activities can reduce these effects (3,23,24,26) . The intestinal effects of pulse consumption are also thought to decrease with experience (20,24,26) , and notably, in systematic reviews of health impacts, few adverse events of pulse consumption are reported (2) .…”
Section: Discussionmentioning
confidence: 58%
“…Third, some activities to challenge preconceptions and increase familiarity may also be of value. These activities could range from increasing awareness of the pulses already contained in popular dishes, such as the beans in chillis or the chickpeas in houmous ( 20 , 22 , 24 , 43 ) , to adding pulses to traditional meat-based recipes on a gradual basis to increase acceptability ( 23 , 28 ) , free food tastings and tasty food offerings ( 22 , 43 ) , and encouraging the provision of pulse-based dishes in scenarios where preparation and cooking are not required, i.e. in out-of-home food outlets such as workplace canteens and restaurants ( 21 , 22 , 24 , 43 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Legumes are a very good source of plant protein with high biological value and complex carbohydrates, while being low in fat [21]. These products, when properly composed with cereal products to complement the amino acid composition of legume seed proteins, can be an alternative choice to high meat consumption, especially red meat [21]. However, it is recommended to consume them peeled or after squeezing them through a sieve, preceded by long cooking [13].…”
Section: The Mediterranean Dietmentioning
confidence: 99%
“…Wawryka et al indicate, in the recommendations, an increase of the content of pulses in the diet due to their health-promoting properties and taste qualities [ 57 ]. The recommendations suggested that natural concerns, as well as motives related to health and weight control, were important for adopting and maintaining a potentially more balanced and healthy diet [ 20 , 58 , 59 , 60 , 61 ]. In the model proposed by the authors, “nutrition and health benefits of pulse products” was the highest-rated variable determining the motives of consumption.…”
Section: Discussionmentioning
confidence: 99%